Health Related Quality of Life of Adult Client Living with Sickle Cell Disease in a Hospital at Banke District, Nepal - K.C., Ishwori; Pokharel, Arati; Shrestha, Durga Laxmi; Pande, Rajan; Panth, Asha; Gautam, Kanchan (Journal of Advanced Academic Research, 2022)
Background: Sickle-cell disease is characterized by a modification in the shape of the red blood cell from a smooth shape into a crescent shape. The misshapen cells lack plasticity and can block small blood vessels, impairing blood flow. The purpose of the study was to find out the quality of life of client living with sickle cell disease. Method: A descriptive cross sectional quantitative study design was used. Non probability convenient sampling technique was used for the selection of respondents after conforming hemoglobin electrophoresis report attending out-patient department of Bheri Hospital. Results: A total 143 participants were studied who were at age range of 19 to 40 years with mean age of 30.26±8.42. Almost 81.8% perceived their health was only fair in comparison to past year. In comparison to other people 60.1% participants believe they get sick little easier. The overall quality of life was good in 56% participants. The health related quality of life scores for eight domains are as follows-physical functioning (77.25±18.22), social functioning (58.39±16.77), role limitation due to emotional problem (57.23±33.99), pain (56.43±22.84), role limitation due to physical problem (49.56±29.76), emotional wellbeing (49.59±14.5), Vitality (36.62±16.85) and general health (36.78±19.99). Conclusion: Quality of life of adults with sickle cell disease is better in the domain of physical function in comparison to other domains. The aspect of energy scale indicates poor quality of life. Female and uneducated clients should be focused for improvement in all domains.